IMPROVING LISTENING SKILL THROUGH DISCOVERY LISTENING TECHNIQUE - Dwi Putri Hartiningsari (STKIP PGRI Trenggalek, 2018)
The objective of the research is to improve students’ listening skill through Discovery Listening Technique. The research design was action research. This method was for improving and modifying the quality of teaching and learning listening comprehension. The subjects of this research were the students of the second semester of English Education Department in the academic year 2015/2016 STKIP PGRI Trenggalek. The procedures of research were planning, implementing, analyzing, and reflecting. By implementing three phases of discovery listening technique, the students could improve their listening skill. It can be known by the improvement of the score from diagnostic test, cycle1 and cycle 2. The mean score of Diagnostic test was 65.7, then 68 in Cycle 1, and 75.33 in cycle 2. Further, the result of questionnaire showed that the students never applied this technique before, discovery listening technique is very helpful for improving listening skill, it is also good for increasing their critical thinking, they have higher motivation for learning listening and it is challenging, and they want to apply this technique continuously